Revision neural monitored surgery for recurrent thyroid cancer: Safety and thyroglobulin response. (26th November 2015) - Salari, Behzad; Ren, Yin; Kamani, Dipti; Randolph, Gregory W.
Abstract : Objectives/Hypothesis: To evaluate the quantitative biochemical response, recurrence rate, and rate of surgical complications for thyroid cancer revision surgery. Study Design: Retrospective review. Methods: This is a single institution analysis of a prospective database of 181 patients undergoing reoperation for local recurrent thyroid cancer by the same surgeon from 2004 to 2013 with intraoperative neural monitoring. Main outcome measures included pathologic findings, surgical complications, effect of reoperation on thyroglobulin (Tg) levels, and recurrence rate. We defined biochemical complete remission as postoperative stimulated Tg of 0.2 ng/mL or less. Results: Fourteen percent of the patients presented with permanent vocal cord palsy (VCP), and 20% of the patients presented with hypocalcemia prior to surgery. Among them, 70% of the patients underwent first revision surgery; whereas in 30% the surgery represented second or higher revision surgery, with 8% being a third or higher revision. None developed temporary or permanent VCP. Temporary hypocalcemia occurred in 9% of the patients, and permanent hypocalcemia occurred in 4.2%. The rate of cervical node recurrence was 5% at a median follow‐up of 3.4 years. There were no disease‐specific deaths. Mean preoperative basal Tg was 22.3 ng/mL and mean postoperative Tg was 5.7 ng/mL, a decline of 74% ( P = 0.023, paired t test). Biochemical complete remission was achieved in 58% of all revision cases. Conclusion: Reoperative neural monitored surgery for recurrent thyroid cancer is a safe and effective procedure with limited morbidity in experienced hands, even in the setting of multiple prior revision surgeries and existing comorbidities such as VCP and hypocalcemia. Level of Evidence: 4. Laryngoscope, 126:1020–1025, 2016